2017
DOI: 10.4301/s1807-17752017000200002
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Interaction Between Business Intelligence and Smes: Learn From Each Other

Abstract: Business Intelligence (BI) and SMEs are two distinctive research domains but greater interaction between these two entities can offer the effective learn from each other. This interaction has been consider in conducting the changing environment. This interaction does only strengthen individual insights of BI and SMEs, it contributes to the business environmental performance. Although research on BI and SMEs is vast to date, limited focus was given on learning aspect between BI and SMEs. Therefore, this study i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 38 publications
0
4
0
1
Order By: Relevance
“…The evidence compiled over the years suggests that innovation flourishes from the seeds of creativity (Stojcic et al, 2018) and knowledge (Santos-Rodrigues et al, 2010) and is found within and outside (Brink, 2017;Tobiassen and Pettersen, 2018) of organizations. Among the internal drivers of innovation, considerable attention has been paid to knowledge (Radas and Božić, 2009), business intelligence (Huges, 2009;Mohsin et al, 2015;Agostino et al, 2013;Ali et al, 2017) and the personal values of staff and managers (Potocan and Nedelko, 2013;Letonja et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The evidence compiled over the years suggests that innovation flourishes from the seeds of creativity (Stojcic et al, 2018) and knowledge (Santos-Rodrigues et al, 2010) and is found within and outside (Brink, 2017;Tobiassen and Pettersen, 2018) of organizations. Among the internal drivers of innovation, considerable attention has been paid to knowledge (Radas and Božić, 2009), business intelligence (Huges, 2009;Mohsin et al, 2015;Agostino et al, 2013;Ali et al, 2017) and the personal values of staff and managers (Potocan and Nedelko, 2013;Letonja et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Tabla 2. Metodologías usadas inteligencia de negocios y analítica de datos en procesos empresariales Metodología de análisis de datos Estudios Metodología Empírica (Ali et al, 2017), (Llave, 2017), (Guitarra Romero, 2019), (Cerda-Leiva et al, 2020), (Popovič et al, 2019), (Ghashami et al, 2019), (Vanegas et al, 2020), (Vanegas et al, 2020), (Torres et al, 2018), (Amankwah-Amoah y Adomako, 2019), (Grytz y Krohn-Grimberghe, 2017), (Verma et al, 2019), (Moreno et al, 2020), (Muñoyerro-Muñiz et al, 2020), (Combita Niño et al, 2020), (Balachandran y Prasad, 2017), (Choi et al, 2020), (Mansell y Ruhode, 2019), (Vajirakachorn y Chongwatpol, 2017), (Václav et al, 2021) Modelo de DeLone y McLean, Modelo de Seddon y Seddon Modificado (Ain et al, 2019), (Gonzales y Wareham, 2019), (Gaardboe et al, 2017) Metodología CRISP-DM (Espinosa Zúñiga, 2020), (Barrera-Narváez et al, 2020) Kimball (Radenković et al, 2018), (Lokaadinugroho et al, 2021) Proceso Unificado Ágil (Morales Lugo et al, 2020), (Sigler et al, 2020) Otras metodologías (Soh and Markus, DTS, TOE, Adaptive Business Intelligence, DSRM, Poe, A-BI+, PMS, Cuadro de Mando integral) (Trieu, 2017), (Pappas et al, 2018), (Ahmad et al, 2020, (Lopes et al, 2020), (Zheng et al, 2018), (Morales y Carrión, 2020), (Francia et al, 2020), (Vallurupalli y Bose, 2018), (Lea et al, 2018) Fuente: elaboración propia. De acuerdo a la Tabla 3, las grandes empresas en los sectores comerciales, servicios de TI, big data, contabilidad, telecomunicaciones, recur...…”
Section: Sectoresunclassified
“…Qushem et al [44] identified the factors involved in determining the efficiency of BI in SMEs; however, only explores Malaysian SMEs. Ali, Khan & Miah [45], aimed to determine the effects and interactions of the relationship between BI and SMEs in the business context. Their results show that SMEs need to improve their capabilities (organizational and technological) for new BI innovations and to select the appropriate BI application to generate competitive advantages.…”
Section: Decision Support System (Dss)mentioning
confidence: 99%